A multiscale interfacial bond for integrally forming aluminum alloys with carbon fiber composites, structures, and methods of processing
Patent Information
- Application Number
- CN202611138271.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
公开研究表明,界面耐久性受相邻材料热膨胀失配、氧化层孔结构、表面羟基密度、水分渗入、金属腐蚀和聚合物链段状态变化共同影响;仅有开放孔结构而缺少后续底涂和阻湿设计时,长期保强率会显著下降
1.五层协同,界面性能全面提升。本发明首次将宏观机械锁合、微纳活化、绝缘防腐底涂、绝缘隔离增强层和阻湿封边层五个功能层次集成于同一界面体系中。宏观锁合提供抗剥离锚固,微纳活化提升化学键合与渗透,绝缘底涂阻断电偶腐蚀并增强界面相容性,隔离增强层增加断裂韧性并进一步绝缘,阻湿封边层抑制湿热老化与边缘起翘。五者协同作用,使得初始剪切强度、剥离强度、湿热老化保持率、冷热冲击保持率和绝缘电阻均显著优于单一或组合不全的对比方案。
Smart Images

Figure CN122976121A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of dissimilar material joining and integral molding technology of metal and fiber reinforced composite materials, and particularly to a multi-scale locking interface, structural component and processing method for integral molding of aluminum alloy and carbon fiber composite materials. Background Technology
[0002] Existing methods for joining aluminum alloys and carbon fiber composites mainly follow these approaches: First, forming a micron / nano-scale activated surface through chemical treatment or anodizing of the aluminum surface, followed by interfacial bonding using resins such as epoxy or adhesive layers; Second, forming protrusions, perforations, recesses, convexities, or grooves on the metal surface, and then filling them with resin to form mechanical anchoring; Third, introducing silane or sol-gel primers onto the aluminum surface to improve chemical coupling and durability; Fourth, placing an insulating layer between the CFRP and the metal to mitigate galvanic corrosion. While existing disclosures cover these individual approaches, a scheme is still lacking that integrates these approaches into a unified interfacial system using a five-layer synergistic approach: macroscopic bonding, micro / nano activation, insulation and corrosion protection, isolation and toughening, and moisture-barrier edge sealing.
[0003] For the interface of aluminum alloy and carbon fiber composites, long-term failure is usually not only manifested as insufficient initial strength, but also more often as interfacial delamination, edge warping, resin / oxide layer interface cracking, and performance degradation caused by galvanic corrosion under thermal cycling, humid heat, and salt spray environments. Public research shows that interfacial durability is jointly affected by the thermal expansion mismatch of adjacent materials, oxide layer pore structure, surface hydroxyl density, moisture penetration, metal corrosion, and changes in polymer chain state; when there is only an open pore structure without subsequent primer and moisture barrier design, the long-term strength retention rate will decrease significantly.
[0004] In the field of electronic terminals, publicly available technologies either lean towards the "aluminum alloy frame + microporous surface + carbon fiber mid-frame plate hot-pressing curing" approach or the "carbon fiber reinforced resin matrix + surface metal plating" approach, but neither simultaneously addresses: macroscopic anti-peeling buckle structure, micro-nano pore chemical activation, insulating and anti-corrosion primer, glass fiber / aramid insulating reinforcement layer, and moisture- and heat-resistant edge sealing design. Therefore, under the conditions of lightweighting, thinning, CNC post-processing capability, and surface post-treatment capability, it is still necessary to propose a new interface system. Summary of the Invention
[0005] To address the shortcomings of the prior art, this invention provides a multi-scale locking interface, structural component, and processing method for integral molding of aluminum alloy and carbon fiber composite materials, thereby simultaneously solving the following problems: Firstly, it enhances the initial shear strength, peel strength, and impact delamination resistance of aluminum alloy and carbon fiber composite materials. Secondly, it reduces the risk of galvanic corrosion caused by direct electrical contact between aluminum alloy and conductive carbon fiber. Third, improve the durability of the interface under humid heat, thermal shock, salt spray and long-term service conditions; Fourth, this interface system is adaptable to thin-walled shells or frame structures of products such as mobile phones, laptops, tablets, drones, and robots, and is compatible with molding, hot pressing, injection molding, co-curing, and subsequent CNC and post-processing techniques.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, comprising an aluminum alloy component, a carbon fiber composite component, and an interface region located between the two. The interface area includes at least: (a) A macroscopic mechanical locking structure provided on the connecting surface of the aluminum alloy component; (b) Micro-nano activated structures formed on the surface of the macro-mechanical interlocking structure and / or its adjacent surfaces; (c) An insulating and corrosion-resistant undercoating layer covering the micro / nano activated structure; (d) An insulating and reinforcing layer disposed between the insulating and anti-corrosion primer and the carbon fiber composite component; (e) Moisture-barrier sealing layer located at the periphery of the interface area; The resin phase in the carbon fiber composite component fills into the macroscopic mechanical interlocking structure during the integral molding process and forms a mechanical interlock after curing. The insulating and reinforcing layer is disposed at least in the peripheral area of the interface region and / or in the area where the carbon fiber composite material may be exposed, so that the aluminum alloy component and the conductive carbon fibers in the carbon fiber composite material remain electrically insulated within the interface region.
[0007] Furthermore, the macroscopic mechanical locking structure is one or more of the following: dovetail groove, T-groove, serrated groove, undercut blind hole, mushroom cavity, stepped hole, through hole, grid groove, protruding column array, and pin rib array; the opening width of the macroscopic mechanical locking structure is 0.05~2.50mm, the maximum cavity width is 0.08~3.50mm, the depth is 0.03~2.00mm, and the center distance between adjacent structures is 0.10~5.00mm.
[0008] Furthermore, the average pore size of the micro / nano activated structure is 10~500nm, the depth or thickness of the active layer is 20nm~30μm, and the surface roughness Ra is 0.20~8.00μm.
[0009] Furthermore, the insulating and anti-corrosion primer coating comprises one or more of the following: silane coupling agent, zirconium-based metal alkoxide, phosphate, sol-gel precursor, epoxy modified primer resin, polydopamine, and inorganic nano-oxide; the thickness of the insulating and anti-corrosion primer coating is 0.05~10.00μm, and the volume resistivity is 108~1014Ω·cm.
[0010] Furthermore, the insulating and reinforcing layer comprises one or more of the following: glass fiber layer, aramid fiber layer, basalt fiber layer, alumina fiber layer, silica fiber layer, and polyimide nonwoven layer; the thickness of the insulating and reinforcing layer is 10~200μm; and the insulating and reinforcing layer is continuously disposed on the main connection interface and extends to the periphery of the interface area to form an edge, so as to form an anti-damp heat delamination structure together with the moisture-proof sealing layer.
[0011] Furthermore, the moisture-proof sealing layer covers at least one of the following areas: the periphery of the interface area, the exposed area of the through hole, and the exposed fiber area at the cut edge. The moisture-proof sealing layer is one or more of the following: a resin-rich sealing layer, a moisture-proof coating, a partial sealing layer, and a continuous film layer.
[0012] Furthermore, the carbon fiber composite component is a thermosetting carbon fiber composite or a thermoplastic carbon fiber composite; the thermosetting carbon fiber composite is one or more of carbon fiber SMC, carbon fiber BMC, carbon fiber prepreg laminate and carbon fiber molded plate; the thermoplastic carbon fiber composite is one or more of carbon fiber reinforced PA, PPS, PEI, PEEK and LCP.
[0013] The present invention provides a structural component, including the above-mentioned multi-scale locking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, wherein the structural component is a mobile phone frame, a laptop shell, a tablet shell, a drone shell, a robot shell, or a wearable device shell.
[0014] This invention also provides a method for processing multi-scale interlocking interface structures for integral molding of aluminum alloy and carbon fiber composite materials, comprising the following steps: S1. Pre-forming and surface pre-treatment of aluminum alloy components; S2. A macroscopic mechanical locking structure is formed on the surfaces of aluminum alloy components to be connected; S3. Forming micro-nano activated structures on the surface of the macroscopic mechanical locking structure and / or its adjacent surfaces; S4. An insulating and corrosion-resistant base coating is formed on the micro-nano activated structure; S5. An insulating and protective reinforcement layer is arranged on the insulating and anti-corrosion base coating; S6. Hot pressing, molding, injection molding, co-curing or integral composite molding of carbon fiber composite preform, SMC / BMC slurry, prepreg or thermoplastic composite with the aluminum alloy component, so that the resin phase enters the macroscopic mechanical interlocking structure. S7. Perform post-curing and moisture-proof edge sealing treatment.
[0015] Furthermore, the method for forming the micro-nano activated structure in step S3 is one or more of the following: anodic oxidation, plasma electrolytic oxidation, alkaline etching-acid neutralization-oxidation treatment, laser micro-nano texturing, chemical roughening, and sandblasting-oxidation composite treatment; in step S6, the forming temperature of the thermosetting system is 110~190℃, the forming pressure is 2~20MPa, and the holding time is 30~900s; in step S7, the post-curing temperature is 120~220℃, and the post-curing time is 10~240min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. Five-layer synergy for comprehensive improvement in interface performance. This invention is the first to integrate five functional layers—macro-mechanical bonding, micro-nano activation, insulating and anti-corrosion primer, insulating and reinforcing layer, and moisture-barrier edge sealing layer—into a single interface system. Macro-bonding provides anti-peel anchoring, micro-nano activation enhances chemical bonding and penetration, the insulating primer blocks galvanic corrosion and enhances interfacial compatibility, the reinforcing layer increases fracture toughness and further insulates, and the moisture-barrier edge sealing layer inhibits damp heat aging and edge warping. The synergistic effect of these five layers results in significantly better initial shear strength, peel strength, damp heat aging retention rate, thermal shock retention rate, and insulation resistance compared to single or incomplete combinations of comparative solutions.
[0017] 2. Excellent galvanic corrosion inhibition capability. Through the dual isolation of the insulating and anti-corrosion primer and the insulating reinforcing layer (glass fiber or aramid), as well as the sealing of the edge capillary channels by the moisture-barrier sealing layer, direct electrical contact between the aluminum alloy and the conductive carbon fiber is effectively blocked. In the embodiment, the interface insulation resistance reaches 10 Ω·cm. 9 ~10 10 The salt spray corrosion spread width is controlled at the Ω level, and is within 0.35~0.70mm.
[0018] 3. Excellent long-term environmental durability. The interface system of this invention retains more than 82% of its shear strength after 500 hours of humid heat at 85℃ / 85%RH, and more than 84% of its strength after 300 cycles of thermal shock from -40℃ to 85℃. This high durability stems from the chemically stable bonding between the micro / nano activated structure and the base coating, the stress concentration mitigation provided by the isolation reinforcement layer, and the inhibition of moisture intrusion by the moisture-barrier sealing layer.
[0019] 4. Broad process compatibility. This invention is compatible with thermosetting and thermoplastic carbon fiber composite systems, and the molding processes can cover compression molding, hot pressing, injection molding, co-curing, etc. It is suitable for a variety of thin-walled structural parts, from mobile phone frames to drone shells, and is highly compatible with existing consumer electronics structural component production lines. Attached Figure Description
[0020] Figure 1 This is a schematic cross-sectional view of the multi-scale locking interface structure of the present invention; Figure 2 A partially enlarged schematic diagram of a dovetail groove on the surface of an aluminum alloy component; Figure 3 A partially enlarged schematic diagram of a composite structure of undercut blind holes and through holes on the surface of an aluminum alloy component; Figure 4 A magnified schematic diagram of a portion of the surface of a macroscopic mechanical interlocking structure after the formation of a micro-nano activated structure. Figure 5 A schematic diagram of the interface where an insulating and anti-corrosion primer coating covers a micro / nano activated structure; Figure 6 A schematic diagram of the interface after the glass fiber / aramid insulation reinforcement layer has been installed; Figure 7 A schematic diagram of a macroscopic mechanically interlocking structure filled with resin phase after integral molding, forming a multi-scale interface; Figure 8 A schematic diagram of setting a moisture-proof edge sealing layer around the interface; Figure 9 This is a flowchart of the method of the present invention; Figure 10 This is a schematic diagram illustrating the application of the present invention to the housings of mobile phones, laptops, tablets, drones, and robots. Detailed Implementation
[0021] The present invention provides a multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, including an aluminum alloy component, a carbon fiber composite component, and an interface region located between the two.
[0022] In this invention, the interface area includes at least: (a) A macroscopic mechanical locking structure provided on the connecting surface of the aluminum alloy component; (b) Micro-nano activated structures formed on the surface of the macro-mechanical interlocking structure and / or its adjacent surfaces; (c) An insulating and corrosion-resistant undercoating layer covering the micro / nano activated structure; (d) An insulating and reinforcing layer disposed between the insulating and anti-corrosion primer and the carbon fiber composite component; (e) Moisture-barrier sealing layer located at the periphery of the interface area; The resin phase in the carbon fiber composite component fills into the macroscopic mechanical interlocking structure during the integral molding process and forms a mechanical interlock after curing. The insulating and reinforcing layer is disposed at least in the peripheral area of the interface region and / or in the area where the carbon fiber composite material may be exposed, so that the aluminum alloy component and the conductive carbon fibers in the carbon fiber composite material remain electrically insulated within the interface region.
[0023] In this invention, the macroscopic mechanical locking structure is one or more of the following: dovetail groove, T-groove, serrated groove, undercut blind hole, mushroom cavity, stepped hole, through hole, grid groove, protruding column array, and pin rib array; the macroscopic mechanical locking structure is formed by CNC milling, rolling, stamping, laser processing, electrical discharge texturing, die casting in-situ forming, or a combination of two or more processes; preferably, CNC or laser processing is used; the opening width of the macroscopic mechanical locking structure is 0.05~2.50mm, preferably 0.10~1.20mm; the maximum cavity width is 0.08~3.50mm, preferably 0.15~1.80mm; the depth is 0.03~2.00mm, preferably 0.08~1.20mm; the center distance between adjacent structures is 0.10~5.00mm, preferably 0.30~2.50mm. The dovetail groove is preferably used in edge areas, corner areas and high warping risk areas with high peeling risk; the T-groove is preferably used in planar overlap and local reinforcement areas; the through hole is preferably used in thick-walled areas that require double-sided mechanical riveting; the undercut blind hole and mushroom cavity are preferably used on the inside of thin-walled parts because they can provide strong anchoring without penetrating the outer surface.
[0024] In this invention, the average pore size of the micro / nano activated structure is 10-500 nm, preferably 20-180 nm; the depth or thickness of the active layer is 20 nm-30 μm, preferably 0.10-8.00 μm; and the surface roughness Ra is 0.20-8.00 μm, preferably 0.40-4.50 μm. The micro / nano activated structure is simultaneously distributed on the inner wall, bottom, and peripheral plane of the macroscopic mechanical interlocking structure to increase the interfacial contact area, resin penetration depth, and interfacial reaction site density. The formation method of the micro / nano activated structure is one or more of the following: anodizing, plasma electrolytic oxidation, alkaline etching-acid neutralization-oxidation treatment, laser micro / nano texturing, chemical roughening, and sandblasting-oxidation composite treatment. Anodizing or alkaline etching-acid neutralization-oxidation treatment is preferred; plasma electrolytic oxidation is more preferred in scenarios requiring higher corrosion resistance; and sulfuric acid-based or phosphoric acid-containing anodizing systems are even more preferred.
[0025] In this invention, the insulating and anti-corrosion primer coating comprises one or more of the following: silane coupling agent, zirconium-based metal alkoxide, phosphate, sol-gel precursor, epoxy-modified primer resin, polydopamine, and inorganic nano-oxide; the insulating and anti-corrosion primer coating can be a single layer or a multilayer; the single-layer primer coating is a silane layer, a zirconium silicate sol-gel layer, a polydopamine layer, an epoxy primer coating, or a thin layer of inorganic oxide; the multilayer primer coating is a silane layer superimposed on a conversion layer / oxidation layer, a low-modulus epoxy transition layer superimposed on a silane layer, or an organic functional layer superimposed on an inorganic thin layer; preferably, a sol-gel system containing epoxy functional group silane and zirconium-based metal alkoxide is used; more preferably, a sol-gel type primer coating containing 3-glycidyl etheroxypropyltrimethoxysilane and zirconium alkoxide is used; further preferably, insulating nano-SiO2, Al2O3, BN, or a combination thereof are added to the primer coating to improve barrier properties and dielectric stability. The thickness of the insulating and anti-corrosion primer is 0.05~10.00μm, preferably 0.20~3.00μm; the volume resistivity is 10. 8 ~10 14 Ω·cm, preferably 10 9 ~10 13 Ω·cm.
[0026] In this invention, the insulating reinforcement layer comprises one or more of the following: a glass fiber layer, an aramid fiber layer, a basalt fiber layer, an alumina fiber layer, a silica fiber layer, and a polyimide nonwoven layer; preferably, a glass fiber layer and / or an aramid fiber layer; more preferably, a composite layer of glass fiber mat and aramid paper. The advantages of the glass fiber layer are good dielectric stability, low cost, and high compatibility with epoxy and various thermosetting / thermoplastic resins; the advantages of the aramid fiber layer are stronger impact resistance, tear resistance, and tear tip propagation resistance; the combination of the two provides a balance of electrical insulation, rigidity, and toughness. The thickness of the insulating reinforcement layer is 10~200μm, preferably 20~120μm; the insulating reinforcement layer can completely cover the connection interface, or it can only cover the peripheral area, high humidity area, high potential difference area, or area with exposed fiber risk at the cut edge; preferably, it completely covers the main connection interface and forms an edge banding at the edge; more preferably, a glass fiber layer is used at the main connection interface, and an aramid layer is used at the edge and corner, forming a combined structure of "glass fiber main insulation + aramid edge toughening". The insulating and protective reinforcement layer is continuously disposed on the main connection interface and extends to the periphery of the interface area to form a edging, so as to form a moisture-proof sealing layer together with the moisture-proof sealing layer to form a moisture-proof delamination-resistant structure.
[0027] In this invention, the moisture-barrier edge sealing layer covers at least one of the following areas: the periphery of the interface area, the exposed area of the through hole, and the exposed fiber area at the cut edge. The moisture-barrier edge sealing layer is one or more of the following: a resin-enriched edge sealing layer, a moisture-proof coating, a partial edge-wrapping layer, and a continuous thin film layer; preferably, it is a composite structure of a resin-enriched edge sealing layer and a moisture-proof outer coating; more preferably, it is a glass fiber / aramid isolation layer extending to cover the edge before being superimposed with a low-absorption edge sealing resin. The moisture-barrier edge sealing layer preferably uses a low-absorption resin, which is one or more of the following: modified epoxy, cyanate ester, benzoxazine, fluorinated polyurethane, and silicone-containing weather-resistant coating; more preferably, sheet-like barrier fillers are added to the moisture-barrier edge sealing layer to extend the moisture diffusion path.
[0028] In this invention, the carbon fiber composite component is a thermosetting carbon fiber composite or a thermoplastic carbon fiber composite; the thermosetting carbon fiber composite is one or more of carbon fiber SMC, carbon fiber BMC, carbon fiber prepreg laminate, and carbon fiber molded plate; the thermoplastic carbon fiber composite is one or more of carbon fiber reinforced PA, PPS, PEI, PEEK, and LCP. For electronic housing, mid-frame, or cover applications, low-water-absorption epoxy, cyanate ester, benzoxazine, or PPS / PEEK resin systems are preferred. The matrix resin in the carbon fiber composite component is preferably a thermosetting or thermoplastic system: in the thermosetting system, the matrix resin is one or more of epoxy, cyanate ester, benzoxazine, bismaleimide, phenolic, and vinyl ester, preferably epoxy, cyanate ester, or benzoxazine; in the thermoplastic system, the matrix resin is selected from one or more of PA, PPS, PEI, PEEK, and LCP, preferably PPS or PEEK.
[0029] The present invention provides a structural component, including the above-mentioned multi-scale locking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, wherein the structural component is a mobile phone frame, a laptop shell, a tablet shell, a drone shell, a robot shell, or a wearable device shell.
[0030] This invention also provides a method for processing multi-scale interlocking interface structures for integral molding of aluminum alloy and carbon fiber composite materials, comprising the following steps: S1. Pre-forming and surface pre-treating the aluminum alloy component; specifically, the aluminum alloy component is one or more of the following: wrought aluminum alloy part, die-cast aluminum alloy part, extruded part, stamped part, and CNC part. Its material includes 1-series to 7-series aluminum alloys and ADC series die-cast aluminum alloys; preferably 5-series, 6-series, or 7-series aluminum alloys; more preferably 5052, 6061, 6063, 7075, and ADC12. The pre-forming includes, but is not limited to, casting, extrusion, stamping, and CNC machining. The surface pre-treatment includes degreasing, washing, and drying. The degreasing solution temperature is preferably 40~70℃, and the treatment time is preferably 1~10 min.
[0031] S2. A macroscopic mechanical interlocking structure is formed on the surface of the aluminum alloy component to be connected; specifically, the macroscopic mechanical interlocking structure is formed by CNC milling, rolling, stamping, etching, laser processing, electrical discharge texturing, die casting in-situ forming, or a combination of two or more processes; preferably, CNC or laser processing is used. For structures with high waterproofing requirements, it is not advisable to use a large number of through holes in exposed areas.
[0032] S3. Forming micro / nano activated structures on the surface of the macroscopic mechanical interlocking structure and / or its adjacent surfaces; specifically, the method for forming the micro / nano activated structures is one or more of the following: anodizing, plasma electrolytic oxidation, alkaline etching-acid neutralization-oxidation treatment, laser micro / nano texturing, chemical roughening, and sandblasting-oxidation composite treatment; preferably, anodizing or alkaline etching-acid neutralization-oxidation treatment is used; more preferably, plasma electrolytic oxidation is used. The anodizing is preferably a sulfuric acid-based or phosphoric acid-containing anodizing system. When using the alkaline etching-acid neutralization-oxidation route, the alkaline concentration is preferably 1~10wt%, and the treatment time is preferably 10~120s; the neutralizing acid concentration is preferably 1~30wt%, and the treatment time is preferably 10~180s. When using the anodizing route, the sulfuric acid concentration in the electrolyte is preferably 50~250g / L, the phosphoric acid concentration is preferably 0~120g / L, the bath temperature is preferably 10~35℃, the voltage is preferably 5~25V, and the time is preferably 1~30min. When using the PEO route, the electrolyte includes one or more of silicates, phosphates, aluminates, and zirconium salts, with a preferred total concentration of 1~80 g / L and a preferred voltage of 150~600 V.
[0033] S4. An insulating and anti-corrosion primer coating is formed on the micro / nano activated structure. Specifically, the insulating and anti-corrosion primer coating is formed by coating, dipping, spraying, roller coating, or electrodeposition. The total amount of organosilane in the primer coating solution is preferably 0.10~10.00wt%, zirconium-based metal alkoxide is preferably 0.05~5.00wt%, acid catalyst is preferably 0.01~3.00wt%, and the remainder is water and / or alcohol solvent. After coating, it is preferably cured at 120~180℃ for 5~20min to form a primer coating with a thickness of 0.05~10.00μm.
[0034] S5. An insulating and reinforcing layer is arranged on the insulating and anti-corrosion primer; specifically, the insulating and reinforcing layer is arranged by laying, attaching, or placing in the mold. The insulating and reinforcing layer may completely cover the connection interface, or it may only cover the peripheral area, high humidity area, high potential difference area, or area with exposed fiber risk at the cut edge; preferably, it completely covers the main connection interface and forms an edge banding at the edge.
[0035] S6. The carbon fiber composite preform, SMC / BMC pellets, prepreg, or thermoplastic composite material are hot-pressed, molded, injection-pressed, co-cured, or integrally composite-molded with the aluminum alloy component, allowing the resin phase to enter the macroscopic mechanical interlocking structure. Specifically, the molding temperature of the thermosetting system is 110~190℃, preferably 150℃; the molding pressure is 2~20MPa, preferably 10MPa; the holding time is 30~900s, preferably 100~800s, and more preferably 300~600s. The molding temperature of the thermoplastic system is in the range of 10~120℃ above the resin melting point. After molding, the resin phase fully fills the cavity of the macroscopic mechanical interlocking structure under pressure and forms a three-dimensional mechanical interlock after curing. For thermosetting systems, post-curing treatment can be performed after demolding.
[0036] S7. Perform post-curing and moisture-proof edge sealing treatment; specifically, the post-curing temperature is 120~220℃, preferably 150~200℃; the post-curing time is 10~240min, preferably 50~200min, and more preferably 100~150min. Moisture-proof edge sealing treatment is performed in at least one area among the interface periphery, the exposed area of the through-hole, and the exposed fiber area at the cut edge. Moisture-proof edge sealing treatment can be performed simultaneously with post-curing or separately after post-curing.
[0037] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0038] Example 1
[0039] Multi-scale locking structure for mobile phone mid-frame interface (I) Structural Composition The substrate is 6063-T6 aluminum alloy with a thickness of 1.20 mm. A unidirectional dovetail groove is formed on the inner side of the surfaces to be joined using CNC machining, with an opening width of 0.35 mm, a maximum cavity width of 0.62 mm, a depth of 0.45 mm, and a center-to-center spacing of 1.20 mm. Then, mixed acid anodizing is performed on the inner wall and surrounding plane of the dovetail groove, resulting in a micro / nano activated layer with an average pore size of 65 nm, a layer thickness of 1.80 μm, and a surface roughness Ra of 1.2 μm. A zirconium silicate sol-gel undercoat is then coated, with a dry film thickness of 0.80 μm and a volume resistivity of approximately 2 × 10⁻⁶. 10Ω·cm. A 38μm thick E-glass fiber mat is laid on the base coating. The composite material uses epoxy-based short-cut carbon fiber (SMC) with a carbon fiber mass fraction of 58% and an average fiber length of 25mm. A 120μm thick resin-enriched edge-sealing layer is applied around the interface, and a 60μm moisture-proof outer coating is applied to its outer surface.
[0040] (II) Preparation steps S1. The 6063-T6 aluminum alloy billet is CNC machined into shape, and then subjected to degreasing, water washing, and drying pretreatment in sequence. The degreasing solution temperature is 60℃, and the treatment time is 5 minutes.
[0041] S2. A dovetail groove array is formed on the aluminum alloy surface to be connected by CNC milling. The parameters of the dovetail groove are: opening width 0.35mm, maximum cavity width 0.62mm, depth 0.45mm, and center spacing 1.20mm.
[0042] S3. The aluminum alloy parts are immersed in a mixed acid electrolyte for anodizing treatment. The electrolyte has a sulfuric acid concentration of 150 g / L and a phosphoric acid concentration of 30 g / L. The bath temperature is 20℃, the voltage is 18V, and the treatment time is 15 min, forming a micro-nano activated structure. The average pore size of this micro-nano activated structure is 65 nm, and the layer thickness is 1.80 μm.
[0043] S4. A zirconium silicate sol-gel primer is applied by dip coating. The primer contains 3-glycidyl etheroxypropyltrimethoxysilane and zirconium alkoxide. The primer is cured at 150°C for 10 min to form an insulating and anti-corrosion primer with a dry film thickness of 0.80 μm.
[0044] S5. Lay a 38μm thick E-glass fiber mat on the primer layer and gently press it down to ensure it adheres tightly to the primer layer.
[0045] S6. Place the epoxy-based short-cut carbon fiber (SMC) pellets into the mold, insert the aluminum alloy parts, close the mold, and press for 240 seconds at 145℃ and 8MPa to allow the resin to flow fully and fill the dovetail groove, and then cure and form.
[0046] S7. After demolding, cure at 150℃ for 30 minutes, then coat the perimeter of the interface with sealing resin (modified epoxy). After curing, a 120μm resin enrichment layer is formed, and then a 60μm moisture-proof outer coating (fluorine-modified polyurethane) is applied.
[0047] Example 2
[0048] Multi-scale locking structure for the back cover interface of a flat panel (I) Structural Composition The substrate is 6061-T6 aluminum alloy with a thickness of 1.50 mm. A composite structure of T-grooves and undercut blind holes is formed on the connecting surface through laser processing: the T-groove opening width is 0.28 mm, the maximum cavity width is 0.54 mm, and the depth is 0.42 mm; the undercut blind hole opening diameter is 0.30 mm, the bottom diameter is 0.55 mm, and the depth is 0.50 mm. Subsequent alkaline etching-acid neutralization-oxidation treatment is performed, resulting in a micro / nano activated layer with an average pore size of 48 nm and a layer thickness of 1.10 μm. The base coating is a silane / epoxy composite base coating with a dry film thickness of 0.55 μm. The insulating and reinforcing layer is made of aramid paper with a thickness of 42 μm. The composite material is epoxy-based carbon fiber (BMC) with a carbon fiber mass fraction of 46% and an average fiber length of 12 mm. The interface perimeter is covered with 95 μm of sealing resin.
[0049] (II) Preparation steps S1. The 6061-T6 aluminum alloy billet is CNC machined to a size of 161.0mm × 76.8mm and a thickness of 1.50mm, and then pre-treated by degreasing, washing with water, and drying. The degreasing solution temperature is 60℃ and the treatment time is 5min.
[0050] S2. A composite locking structure of T-slot and undercut blind hole is formed on the aluminum alloy surface to be connected by laser processing: the T-slot opening width is 0.28mm, the maximum cavity width is 0.54mm, and the depth is 0.42mm; the undercut blind hole opening diameter is 0.30mm, the bottom diameter is 0.55mm, and the depth is 0.50mm.
[0051] S3. The aluminum alloy parts are subjected to alkaline etching-acid neutralization-oxidation treatment: First, they are immersed in 5wt% NaOH alkaline solution for 60s, washed with water, and then immersed in 15wt% HNO3 neutralization solution for 90s. Then, sulfuric acid anodizing treatment is performed (sulfuric acid concentration 150g / L, voltage 15V, time 10min) to form a micro-nano activated structure with an average pore size of 48nm and a layer thickness of 1.10μm.
[0052] S4. Apply silane / epoxy composite primer by spraying and cure at 140℃ for 15 minutes to form an insulating and anti-corrosion primer with a dry film thickness of 0.55μm.
[0053] S5. Lay aramid paper with a thickness of 42μm on the base coating and gently press it to adhere to the base coating.
[0054] S6. Place the epoxy-based carbon fiber (BMC) pellets into the mold, insert the aluminum alloy parts, close the mold, and then press for 210 seconds at 150℃ and 10MPa to allow the resin to fill and lock the structure, and then cure and form.
[0055] S7. After demolding, cure at 160℃ for 25 minutes, then coat the perimeter of the interface with sealing resin (modified epoxy), and after curing, form a 95μm sealing layer.
[0056] Example 3
[0057] Multi-scale locking structure for laptop A-side / top cover reinforcement shell (I) Structural Composition The substrate is made of 5052-H32 aluminum alloy with a thickness of 1.00 mm. A sawtooth groove array is formed through a combination of rolling and CNC machining, with an opening width of 0.40 mm, a depth of 0.35 mm, and a center-to-center spacing of 1.60 mm. After anodizing with phosphoric acid, the micro / nano activated layer has an average pore size of 72 nm and a layer thickness of 2.20 μm. The base coating uses a zirconium silicate sol-gel primer with a dry film thickness of 0.95 μm. The insulating and reinforcing layer is a composite layer of glass fiber felt and aramid (total thickness 58 μm). The composite material uses a composite structure of cyanate ester-based carbon fiber prepreg and a BMC transition layer. A 140 μm resin-enriched edge-sealing layer is used at the interface perimeter.
[0058] (II) Preparation steps S1. Roll forming and CNC precision machining are performed on the 5052-H32 aluminum alloy billet to produce an outer perimeter frame with a thickness of 1.00mm. The frame is then subjected to degreasing, water washing, and drying pretreatment. The degreasing solution temperature is 55℃, and the treatment time is 6 minutes.
[0059] S2. A serrated groove array is formed on the aluminum alloy surface to be joined by a combination of rolling and CNC processes. The serrated groove opening width is 0.40mm, the depth is 0.35mm, and the center spacing is 1.60mm.
[0060] S3. Immerse the aluminum alloy parts in an anodizing electrolyte containing phosphoric acid for treatment: phosphoric acid concentration 80g / L, sulfuric acid concentration 50g / L, bath temperature 25℃, voltage 20V, time 20min, to form a micro-nano activated structure with an average pore size of 72nm and a layer thickness of 2.20μm.
[0061] S4. Apply zirconium silica sol-gel primer (containing 3-glycidyl etheroxypropyltrimethoxysilane and zirconium alkoxide) by dip coating and cure at 150°C for 12 min to form an insulating and anti-corrosion primer with a dry film thickness of 0.95 μm.
[0062] S5. Lay a composite layer of fiberglass felt and aramid layer (38μm thick fiberglass layer, 20μm thick aramid layer) on the base coating and gently compact it.
[0063] S6. The cyanate ester-based carbon fiber prepreg is laid in the main load-bearing area, the BMC transition layer material is laid in the edge transition area, the aluminum alloy part is placed in, and after the mold is closed, it is cured for 300 seconds at 155℃ and 7MPa to allow the resin to fully fill the serrated groove.
[0064] S7. After demolding, cure at 180℃ for 20 minutes, and then coat the perimeter of the interface with sealing resin (cyanate ester modified resin). After curing, a 140μm resin-rich sealing layer is formed.
[0065] Example 4
[0066] Multi-scale locking structure for drone shell (I) Structural Composition The substrate is 7075-T6 aluminum alloy with a thickness of 1.40 mm. A combination of through holes and dovetail grooves with interlocking structure is formed using CNC machining: through hole diameter 0.45 mm, hole spacing 2.20 mm; dovetail groove opening width 0.22 mm, maximum cavity width 0.48 mm, and depth 0.38 mm. A micro / nano activation layer is formed using PEO treatment, with an average pore size of 95 nm and a layer thickness of 4.60 μm. The base coating is a composite base coating containing epoxy-functionalized silane, zirconium alkoxide, and nano-SiO2, with a dry film thickness of 1.10 μm. The insulating and reinforcing layer uses a double-layer structure of a 35 μm thick glass fiber layer and a 20 μm thick aramid layer. The composite material uses benzoxazine-based short-chopped carbon fiber (SMC), with a carbon fiber mass fraction of 54% and an average fiber length of 18 mm.
[0067] (II) Preparation steps S1. The 7075-T6 aluminum alloy blank is CNC machined to form a drone shell frame with a thickness of 1.40mm, and then pre-treated by degreasing, washing, and drying. The degreasing solution temperature is 65℃, and the treatment time is 4min.
[0068] S2. A combination locking structure of through holes and dovetail grooves is formed on the aluminum alloy surface to be connected by CNC machining: the diameter of the through hole is 0.45mm and the hole spacing is 2.20mm; the opening width of the dovetail groove is 0.22mm, the maximum cavity width is 0.48mm, and the depth is 0.38mm.
[0069] S3. Plasma electrolytic oxidation (PEO) treatment is performed on aluminum alloy parts: the electrolyte contains 5g / L silicate and 3g / L phosphate, with a total concentration of 8g / L, the voltage is 450V, the treatment time is 10min, and a micro-nano activation layer is formed with an average pore size of 95nm and a layer thickness of 4.60μm.
[0070] S4. A composite primer is applied by spraying. The primer contains 1.5 wt% epoxy functional group silane, 0.8 wt% zirconium alkoxide, and 0.5 wt% nano SiO2. It is cured at 160°C for 15 min to form an insulating and anti-corrosion primer with a dry film thickness of 1.10 μm.
[0071] S5. Lay a 35μm thick glass fiber layer on the base coating, and then lay a 20μm thick aramid layer on top of it to form a double-layer insulation and reinforcement structure, and gently compact it.
[0072] S6. Place the benzoxazine-based short-cut carbon fiber SMC material into the mold, insert the aluminum alloy part, close the mold, and mold it for 270 seconds at 160℃ and 9MPa to allow the resin to fill and lock the structure, and then cure and form it.
[0073] S7. After demolding, cure at 185°C for 35 minutes. In this embodiment, the insulating reinforcement layer self-seales, and no additional edge sealing layer is required.
[0074] Example 5
[0075] (I) Structural Composition The substrate is an ADC12 die-cast aluminum alloy part with a wall thickness of 2.00 mm. A pre-formed array of protrusions is created within the mold, followed by CNC machining to form local undercut grooves: protrusion diameter 0.60 mm, height 0.40 mm, center-to-center spacing 1.80 mm; undercut groove depth 0.52 mm. The connection area undergoes alkaline etching-acid neutralization-oxidation treatment, resulting in a micro / nano activation layer with an average pore size of 52 nm and a thickness of 1.30 μm. The base coating is a polydopamine / silane composite base coating with a dry film thickness of 0.60 μm. The insulating and reinforcing layer is a 48 μm thick glass fiber nonwoven layer. The composite material is integrally formed using PPS-based long-fiber carbon fiber thermoplastic sheet (43% carbon fiber mass fraction) and the local BMC transition area. A 100 μm moisture-proof edge-sealing layer is applied around the interface.
[0076] (II) Preparation steps S1. Die-cast the ADC12 die-cast aluminum alloy blank to form a robot shell with a wall thickness of 2.00 mm. Pre-form an array of protrusions (protrusion diameter 0.60 mm, height 0.40 mm, center-to-center spacing 1.80 mm) in the mold. Then, perform degreasing, water washing, and drying pretreatment in sequence. The degreasing solution temperature is 60℃, and the treatment time is 5 min.
[0077] S2. A local undercut groove is formed on the aluminum alloy surface to be connected by CNC machining, with a depth of 0.52mm.
[0078] S3. The aluminum alloy parts are subjected to alkaline etching-acid neutralization-oxidation treatment: First, they are immersed in 5wt% NaOH alkaline solution for 60s, washed with water, and then immersed in 15wt% HNO3 neutralization solution for 90s. Then, sulfuric acid anodizing treatment is performed (sulfuric acid concentration 150g / L, voltage 15V, time 10min) to form a micro-nano activated structure with an average pore size of 52nm and a layer thickness of 1.30μm.
[0079] S4. Apply polydopamine / silane composite primer by dip coating and cure at 120℃ for 20 min to form an insulating and anti-corrosion primer with a dry film thickness of 0.60 μm.
[0080] S5. Lay a glass fiber nonwoven layer with a thickness of 48μm on the base coating and gently compact it.
[0081] S6. PPS-based long fiber carbon fiber thermoplastic sheet is laid in the main connection area, local BMC transition area material is laid at the edge, aluminum alloy part is inserted, after mold closing, it is hot-pressed at 315℃ and 6MPa for 210s to melt the resin and fill the locking structure, and then cooled and cured.
[0082] S7. After demolding, apply a moisture-proof sealing layer (fluorine-modified polyurethane) with a thickness of 100μm to the perimeter of the interface and cure at room temperature for 24h.
[0083] Example 6
[0084] Multi-scale locking structure for general electronic housing / mid-frame transition areas (I) Structural Composition The substrate is made of 6061-T6 aluminum alloy with a thickness of 1.30 mm. A stepped hole array is formed through laser processing: hole opening diameter 0.32 mm, hole bottom diameter 0.58 mm, depth 0.46 mm, and hole spacing 1.40 mm. Sulfuric acid anodizing is used, resulting in a micro / nano activated layer with an average pore size of 44 nm and a layer thickness of 1.50 μm. The base coating is a zirconium silicate sol-gel primer with a dry film thickness of 0.70 μm. The insulating and reinforcing layer is a 26 μm thick aramid nonwoven layer. The composite material consists of a PEEK-based carbon fiber reinforced sheet and a locally low-viscosity PEEK transition film. An 85 μm edge-sealing layer is used at the interface perimeter.
[0085] (II) Preparation steps S1. The 6061-T6 aluminum alloy blank is CNC machined to form a shell / middle frame transition area structural component with a thickness of 1.30mm, and then subjected to degreasing, water washing, and drying pretreatment in sequence. The degreasing solution temperature is 60℃, and the treatment time is 5min.
[0086] S2. A stepped hole array is formed on the aluminum alloy surface to be joined by laser processing: hole diameter 0.32mm, hole bottom diameter 0.58mm, depth 0.46mm, and hole spacing 1.40mm.
[0087] S3. Perform sulfuric acid anodizing treatment on aluminum alloy parts: sulfuric acid concentration 150g / L, bath temperature 20℃, voltage 18V, time 15min, to form micro-nano activated structure with average pore size 44nm and layer thickness 1.50μm.
[0088] S4. Apply zirconium silica sol-gel primer (containing 3-glycidyl etheroxypropyltrimethoxysilane and zirconium alkoxide) by dip coating and cure at 150°C for 10 min to form an insulating and anti-corrosion primer with a dry film thickness of 0.70 μm.
[0089] S5. Lay an aramid nonwoven layer with a thickness of 26μm on the base coating and gently compact it.
[0090] S6. Place the PEEK-based carbon fiber reinforced sheet in the main connection area, place the local low-viscosity PEEK transition film on the edge, insert the aluminum alloy part, close the mold, and hot press at 390℃ and 5MPa for 180s to melt the resin and fill the step holes, and then cool and solidify.
[0091] S7. After demolding, apply sealing resin (containing silicone weather-resistant coating) to the perimeter of the interface, and after curing, form an 85μm sealing layer.
[0092] Comparative Example 1 Only a macroscopic mechanical locking structure (dovetail groove) is provided; no micro / nano activation structure is formed; and no insulating and anti-corrosion primer, insulating isolation reinforcement layer, or moisture-proof sealing layer is provided. The rest is the same as in Example 1.
[0093] Comparative Example 2 A micro / nano activated structure is formed and a base coating is applied, but no macroscopic mechanical locking structure, insulation reinforcement layer, or moisture-proof sealing layer is applied. The rest is the same as in Example 1.
[0094] Comparative Example 3 The system includes a macroscopic mechanical locking structure, a micro / nano activation structure, and a base coating, but omits the insulation reinforcement layer and the moisture-barrier edge sealing layer. The rest is the same as in Example 1.
[0095] Performance testing: The single-lap shear specimen size was 100mm×25mm, the overlap length was 12.5mm, and the loading speed was 1mm / min; the peel performance was tested using a 180° peel method at a peel speed of 50mm / min; the damp heat aging conditions were 85℃ / 85%RH for 500h; the thermal shock conditions were -40℃ for 30min and 85℃ for 30min, for a total of 300 cycles; the salt spray conditions were 5wt%NaCl, 35℃, for 240h; the interface insulation resistance was measured using 100V DC for 60s between the aluminum side and the carbon fiber side, and the test results are shown in Table 1.
[0096] Table 1 Performance Test Results
[0097] As can be seen from the above embodiments, the multi-scale interlocking interface of the present invention is not the result of a single point feature, but rather the result of the combined effects of macroscopic mechanical interlocking, micro-nano activation, insulating and anti-corrosion primer, insulating and reinforcing layer, and moisture-barrier sealing layer. In particular, the present invention has more significant advantages over the comparative example in terms of moisture and heat retention rate, thermal shock retention rate, interface insulation resistance, and salt spray edge propagation control.
[0098] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, comprising an aluminum alloy component, a carbon fiber composite component, and an interface region located between the two, characterized in that, The interface area includes at least: (a) A macroscopic mechanical locking structure provided on the connecting surface of the aluminum alloy component; (b) Micro-nano activated structures formed on the surface of the macro-mechanical interlocking structure and / or its adjacent surfaces; (c) An insulating and corrosion-resistant undercoating layer covering the micro / nano activated structure; (d) An insulating and reinforcing layer disposed between the insulating and anti-corrosion primer and the carbon fiber composite component; (e) Moisture-barrier sealing layer located at the periphery of the interface area; The resin phase in the carbon fiber composite component fills into the macroscopic mechanical interlocking structure during the integral molding process and forms a mechanical interlock after curing. The insulating and reinforcing layer is disposed at least in the peripheral area of the interface region and / or in the area where the carbon fiber composite material may be exposed, so that the aluminum alloy component and the conductive carbon fibers in the carbon fiber composite material remain electrically insulated within the interface region.
2. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The macroscopic mechanical locking structure is one or more of the following: dovetail groove, T-groove, serrated groove, undercut blind hole, mushroom cavity, stepped hole, through hole, grid groove, protruding column array, and pin rib array; the opening width of the macroscopic mechanical locking structure is 0.05~2.50mm, the maximum cavity width is 0.08~3.50mm, the depth is 0.03~2.00mm, and the center distance between adjacent structures is 0.10~5.00mm.
3. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The average pore size of the micro / nano activated structure is 10~500nm, the depth or thickness of the active layer is 20nm~30μm, and the surface roughness Ra is 0.20~8.00μm.
4. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The insulating and anti-corrosion primer coating comprises one or more of the following: silane coupling agent, zirconium-based metal alkoxide, phosphate, sol-gel precursor, epoxy-modified primer resin, polydopamine, and inorganic nano-oxide; the thickness of the insulating and anti-corrosion primer coating is 0.05~10.00μm, and the volume resistivity is 10. 8 ~10 14 Ω·cm.
5. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The insulating and reinforcing layer comprises one or more of the following: glass fiber layer, aramid fiber layer, basalt fiber layer, alumina fiber layer, silica fiber layer, and polyimide nonwoven layer; the thickness of the insulating and reinforcing layer is 10~200μm; and the insulating and reinforcing layer is continuously disposed on the main connection interface and extends to the periphery of the interface area to form an edge, so as to form an anti-damp heat delamination structure together with the moisture-proof edge sealing layer.
6. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The moisture-proof sealing layer covers at least one of the following areas: the periphery of the interface area, the exposed area of the through hole, and the exposed fiber area at the cut edge. The moisture-proof sealing layer is one or more of the following: a resin-rich sealing layer, a moisture-proof coating, a partial sealing layer, and a continuous film layer.
7. The multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials according to claim 1, characterized in that, The carbon fiber composite component is a thermosetting carbon fiber composite or a thermoplastic carbon fiber composite; the thermosetting carbon fiber composite is one or more of carbon fiber SMC, carbon fiber BMC, carbon fiber prepreg laminate and carbon fiber molded plate; the thermoplastic carbon fiber composite is one or more of carbon fiber reinforced PA, PPS, PEI, PEEK and LCP.
8. A structural component, characterized in that, Includes the multi-scale locking interface structure for integral molding of aluminum alloy and carbon fiber composite materials as described in any one of claims 1 to 7, wherein the structural component is a mobile phone frame, a laptop shell, a tablet shell, a drone shell, a robot shell, or a wearable device shell.
9. A method for processing a multi-scale interlocking interface structure for integral molding of aluminum alloy and carbon fiber composite materials, as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Pre-forming and surface pre-treatment of aluminum alloy components; S2. A macroscopic mechanical locking structure is formed on the surfaces of aluminum alloy components to be connected; S3. Forming micro-nano activated structures on the surface of the macroscopic mechanical locking structure and / or its adjacent surfaces; S4. An insulating and corrosion-resistant base coating is formed on the micro-nano activated structure; S5. An insulating and protective reinforcement layer is arranged on the insulating and anti-corrosion base coating; S6. Hot pressing, molding, injection molding, co-curing or integral composite molding of carbon fiber composite preform, SMC / BMC slurry, prepreg or thermoplastic composite with the aluminum alloy component, so that the resin phase enters the macroscopic mechanical interlocking structure. S7. Perform post-curing and moisture-proof edge sealing treatment.
10. The processing method according to claim 9, characterized in that, The method for forming the micro-nano activated structure in step S3 is one or more of the following: anodic oxidation, plasma electrolytic oxidation, alkaline etching-acid neutralization-oxidation treatment, laser micro-nano texturing, chemical roughening, and sandblasting-oxidation composite treatment; in step S6, the forming temperature of the thermosetting system is 110~190℃, the forming pressure is 2~20MPa, and the holding time is 30~900s; in step S7, the post-curing temperature is 120~220℃, and the post-curing time is 10~240min.